The burden of rotavirus-associated acute gastroenteritis in the elderly: assessment of the epidemiology in the context of universal childhood vaccination programs - Anna Karakusevic; Patrick Devaney; Ashley Enstone; Nabi Kanibir; Susanne Hartwig; Cristina Da Silva Carias (Taylor & Francis Group, 2022)
ABSTRACTIntroduction Rotaviruses (RVs) cause acute gastroenteritis (AGE) in infants and young children worldwide and also in older adults (≥60 years), however the burden among this age group is not well understood. Herd immunity through pediatric RV vaccination may reduce the burden of RVGE across all ages, however the impact of pediatric vaccination on burden in older adults is poorly understood.Areas covered This systematic review was undertaken to identify studies related to the following objectives: understand the burden of RV in older adults, RV seroprevalence, and the impact of pediatric vaccination on this burden and highlight evidence gaps to guide future research. Of studies identified, 59 studies from two databases were included in this analysis following a review by two reviewers.Expert opinion RV is an understudied disease in older adults. We found that 0-62% of patients with AGE tested positive for RV, with results varying by setting, country, and patient age. Results also suggest that pediatric vaccination benefits older adults through herd protection. Several studies showed a reduction in RV incidence after vaccination. However, there was variety in results and lack of consistency in outcomes reported. Further studies targeting older adults are needed to better characterize RV burden.